Design of spark ignition engine speed control using bat algorithm - Setiadi, Herlambang; Jones, Karl O.; Nugroho, Teguh Aryo; Abdillah, Muhammad; Trilaksana, Herri; Amrillah, Tahta (International Journal of Electrical and Computer Engineering (IJECE), 2021)
The most common problem in spark ignition engine is how to increase the speed performance. Commonly researchers used traditional mathematical approaches for designing speed controller of spark ignition engine. However, this solution may not be sufficient. Hence, it is important to design the speed controller using smart methods. This paper proposes a method for designing speed controller of a spark ignition engine using the bat algorithm (BA). The simulation is carried out using the MATLAB/SIMULINK environment. Time domain simulation is carried out to investigate the efficacy of the proposed method. From the simulation results, it is found that by designing speed controller of spark ignition engine using PI based bat algorithm, the speed performance of spark ignition engine can be enhanced both in no load condition and load condition compared to conventional PI controler.